On examining for transparency or opacity: Attending to sexual-gender diversity in Quito - Paz Guarderas; UPS-Quito (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
Social services in Quito have tended to specialize attention according to population groups. Sexual-gender diversity has been no exception. In this article, we attempt to demonstrate, using narrative productions, the ways sexual-gender diversity has been understood in services offered to victims of gender based violence and in psychological attention. The major findings reveal a reductionist view of gender based violence which implies an absence or an invisibilization of sexual-gender diversity in services offered. In terms of understandings of this diversity, there is a tendency toward teleological, essentialist, and univocal readings which nevertheless coexist with certain notions of complexity. Finally, it is clear that psychological actions tend toward the normalization of gender but that the p